2002
DOI: 10.1111/j.1939-165x.2002.tb00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Chemistry of Companion Avian Species: A Review

Abstract: Birds have evolved alternate physiologic strategies to contend with dehydration, starvation, malnutrition, and reproduction. Basic anatomic and functional differences between birds and mammals impact clinical chemistry values and their evaluation. Interpretation of the results of standard biochemical analyses, including BUN, alanine aminotransferase, aspartate aminotransferase, creatine kinase, gamma glutamyltransferase, bilirubin, ammonia, alkaline phosphatase, cholesterol, bile acids, glucose, albumin, globu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
200
1
30

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(245 citation statements)
references
References 65 publications
14
200
1
30
Order By: Relevance
“…Uric acid is the main product of protein nitrogen and purine metabolism in poultry. Approximately 90% of the uric acid is secreted by the proximal convoluted tubules in healthy broilers (Harr, 2002). The highest values found in males may reflect their protein metabolism rate at this age, as they have a higher body growth rate than females.…”
Section: Serum Biochemical Parametersmentioning
confidence: 94%
See 2 more Smart Citations
“…Uric acid is the main product of protein nitrogen and purine metabolism in poultry. Approximately 90% of the uric acid is secreted by the proximal convoluted tubules in healthy broilers (Harr, 2002). The highest values found in males may reflect their protein metabolism rate at this age, as they have a higher body growth rate than females.…”
Section: Serum Biochemical Parametersmentioning
confidence: 94%
“…According to Peebles et al (2004), the levels of LDL and VLDL, which are lipoproteins associated with the transport of cholesterol, are much lower in males than in females, compared to HDL levels, responsible for the reduction of serum cholesterol. Cholesterol levels can also be influenced by age, diet, and reproductive activity (Harr, 2002;Alonso-Alvarez, 2005). Ross et al (1978) reported cholesterol values of 1.86-3.37 mmol/L in broilers.…”
Section: Serum Biochemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, these enzymes may be adversely affected by factors such as muscular injury, rupture of organs, nutritional status, physical activity, hemolysis, treatment, and conservation of plasma samples and their levels in blood can increase. Also, these enzymes can be an important diagnostic tool in veterinary medicine [15]. Table 3 presents the activity of the investigated enzymes during the period of Se supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…Bile stasis has been described in inflammations, infections, neoplasia, toxic insults, and lipoidosis [55]. Now, inflammation with hepatic amyloidosis can be added to this list.…”
Section: Discussionmentioning
confidence: 99%